THE IMPACT OF GOOD CORPORATE GOVERNANCE ON FRAUD PREVENTION - Zhieren Adziqa As'ad; Erna Sulistyowati (RISTANSI: Riset Akuntansi, 2026)
This study aims to test the impact of good corporate governance (GCG) on fraud prevention at Mining Company X. The sampling approach employed probability sampling with a basic random sampling procedure, yielding 94 respondents from a total of 1,451 permanent employees. This study employs a quantitative method, employing Partial Least Squares (PLS) analysis powered by SmartPLS 4.0 software. The results prove that GCG has a positive and significant effect on fraud prevention, with a p-value of 0.000 and a path coefficient of 0.736. The R² value of 0.542 suggests that GCG moderately contributes to explaining fraud prevention. These results highlight the crucial role of implementing GCG principles in establishing an effective anti-fraud system, particularly in mining companies that face high exposure to fraud risks.